Usefulness of iodine-blood material density images in estimating degree of liver fibrosis by calculating extracellular volume fraction obtained from routine dual-energy liver CT protocol equilibrium phase data: preliminary experience - Ito, Emi; Sato, Keisuke; Yamamoto, Ryotaro; Sakamoto, Keiko; Urakawa, Hiroshi; Yoshimitsu, Kengo (Japanese journal of radiology, 2020)
Purpose To assess whether extracellular volume fraction (ECV) calculated from iodine(-blood) density images (I-B) of dual-energy liver CT (DECT) equilibrium phase data (EqD) is useful in estimating the degree of liver fibrosis. Materials and methods Consecutive 52 patients with chronic liver disease who underwent fast kV switching DECT and liver MR elastography (MRE) were retrospectively enrolled. Iodine(-water) density images (I-W) and I-B generated from EqD and ECV were calculated. As blood pools, abdominal aorta (Ao) and suprahepatic inferior vena cava (IVC) were chosen, and, therefore, 4 types of ECV (ECV I-W Ao , ECV I-W IVC , ECV I-B Ao , ECV I-B IVC ) were obtained. ECV was also calculated using conventional method (ECV conv Ao ). The correlation coefficients ( R 2 or rho) of these five ECVs versus liver stiffness (MRE) or pathologically proven fibrosis grades were compared. Results As for correlation with liver stiffness, R 2 for ECV conv.Ao , ECV I-W Ao , ECV I-B Ao , ECV I-W IVC , and ECV I-B IVC , were 0.26, 0.34, 0.44, 0.39, and 0.52, respectively (all p < 0.0001). Histopathological correlation was available in 28 patients, and rho values were 0.61, 0.60, 0.71, 0.68, and 0.76, respectively (all p < 0.001). Conclusion ECV I–B IVC calculated from EqD of DECT is useful in estimating the degree of liver fibrosis.